The Dynamics of Tri Hita Karana Implementation in The Balinese Hindu Residence in South Denpasar - I Putu Sarjana; I Putu Gelgel; I Wayan Budi Utama (International Journal of Interreligious and Intercultural Studies, 2020)
This article aims to analyze the dynamicity of Tri Hita Karana implementation in South Denpasar regarding the causing factors, the dynamic forms, as well the implication on the Hindus community life. This research was conducted using qualitative methods. The data were collected through document study, observation, and in-depth interviews with 25 informants. The collected data were analyzed by the theories of hegemony, social change, socio-cultural system critical, and adaptation. The results showed: First, the factors causing the dynamicity of Tri Hita Karana in the residential area of Hindus are urban modernization, population growth, spatial planning policies and settlement development, and rationalization in building construction. Second, the dynamics of Tri Hita Karana in these residentials are: (a) In the palemahan area, land conversion has displaced the subak and Ulun Suwi temple, violation of the principles of Balinese Traditional Architecture (ATB), displacing the existence of the open space; b) The pawongan area is characterized by increasingly heterogeneous, multi-ethnic and multi-cultural citizens.; (c) In the parahyangan area where the building layout was not reconstructed, the holy place Merajan was built on the upper floor of the residence. Third, the implications of the dynamics of Tri Hita Karana in the residential area of Hindus in the South Denpasar, include: (a) The palemahan area implies the use of land space based on the principles of effective, efficient, and economical, but the concept of ulu teben and kaja-kangin as the Balinese sacred orientations is still maintained; (b) The pawongan area is characterized by the behavior of city dwellers looking for Social space and spiritual recreation; (c) The Parahyangan area is characterized by praying activities at Merajan and Padmasana on the upper floor of the residence. To enforce the Tri Hita Karana, the misuse (disorientation) of spatial planning needs to be anticipated.